2011
DOI: 10.1097/mpg.0b013e31821dca49
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Community‐based Follow‐up Care in Managing Severely Underweight Children

Abstract: Positioning follow-up services in the community increases follow-up visits and promotes greater linear growth; providing SF, with or without PS, increases clinic attendance and enhances nutritional recovery. Community-based service delivery, especially including SF, permits better rehabilitation of greater numbers of severely underweight children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…After 3 months of intervention, the children who had received food and PS had significantly higher follow-up attendance than the controls, and those who received FS had higher weight gain compared with the other groups (Hossain et al, 2011). In this paper, we present the findings at the end of study, that is, after 6 months of intervention.…”
Section: Introductionmentioning
confidence: 53%
“…After 3 months of intervention, the children who had received food and PS had significantly higher follow-up attendance than the controls, and those who received FS had higher weight gain compared with the other groups (Hossain et al, 2011). In this paper, we present the findings at the end of study, that is, after 6 months of intervention.…”
Section: Introductionmentioning
confidence: 53%
“…Fifteen of the 20 trials had been completed – and the results of four had been published – by the time of our search. 40 43 Two had reported statistically significant results; one demonstrated that community follow-up increased linear growth and clinic attendance 43 and the other that long-chain n -3 polyunsaturated fatty acid in erythrocytes increased among severely malnourished children who were given ready-to-use therapeutic food enriched with polyunsaturated fatty acid. 42 The other two published trials, which detected no significant differences, compared alternative formulations of ready-to-use therapeutic food with standard formulations.…”
Section: Resultsmentioning
confidence: 99%
“…O baixo peso, assim como o peso insuficiente ao nascer, são os principais determinantes da morbimortalidade infantil (26). Quanto a esta última variável, destaca-se a consistência do Índice IPR/ Pré-Natal, no qual ter tido o pré-natal adequado proporciona menores chances de ocorrência desse agravo.…”
Section: Discussionunclassified